Selçuklular Devri Müfessirleri (XI-XIV. yy) - Demireşik, Ömer Faruk (İstanbul Sabahattin Zaim Üniversitesi, 2022)
Dandanakan Savaşı'yla kurulduğu kabul edilen Selçuklu Devleti; Emevî ve Abbâsîleri müteâkiben kurulmuş üçüncü en büyük müslüman devletidir. Bu yönüyle hem Türk-İslam tarihi açısından hem de dünya tarihi açısından büyük önem arz etmektedir. Büyük Selçuklular Devleti ve onun yıkılmasıyla kurulmuş olan Kirman, Anadolu, Suriye ve Irak Selçuklu Devletleri ile yaklaşık üç asır boyunca, çok geniş bir coğrafyaya hükmetmiştir. Bu dönem zarfında sadece kendi hükmettiği topraklarda değil, Mısır, Kuzey Afrika, Endülüs ve Hindistan üzerinde de etkili olmuştur. Selçukluların bu tesiri, birçok alanda çeşitli araştırmalarla incelenmiştir. Ancak yapılan bu araştırmaların çoğu, Selçukluları dînî ilimler sahasında değil; siyasî tarih, devletlerarası ilişkiler, mimarî ve el sanatları gibi farklı yönlerden ele almaktadır. Dînî ilimler alanında yapılan sınırlı çalışmalarda ise tefsir araştırmaları yok denecek kadar azdır. Biz de bu tezimizde, Selçuklu Devleti tarihi ve coğrafyası üzerinden tefsirin geçirdiği merhaleleri ele aldık. Önce zaman, mekân ve kavram sınırlarını çizdik. Sonra da tabakat, tarih kitapları, ansiklopediler ve diğer akademik kaynaklar üzerinden çalışmamızı şekillendirdik. Araştırmamızın sonucunda, Selçukluların ilim, kültür ve medeniyet tarihi üzerinde derin izleri olduğu gibi, tefsir ilminin gelişimi ve yayılması hususunda büyük katkıları olduğunu tesbit ettik. Kurduğu müesseseler, yetiştirdiği devlet ve ilim adamlarıyla İslâmî ilimlerin ve dolayısıyla tefsir ilminin işleyişine doğrudan müdahale etmiştir. Bu dönem, ulaştığı seviye ile dînî ilimlerin zirvesini teşkil etmiş, ancak iç savaşlar, göçler, Moğol ve Haçlı Seferleri ile başlayan duraklama devri, maalesef günümüze kadar devam etmiştir.

After the victory of the Saljuqs over the Ghaznavids at Dandānaqān, the Saljuk family gained a great power and established the state which is going to rise as the third biggest Muslim state, following Umayyads and 'Abbāsids. Saljuqs'. From this aspect, Saljuqs present a grand significance and prominent role on both Islamic and world history. The Kirmans, Anatolian, Syrian and Iraqi Saljuqs –which established after the collapse of The Great Saljuqs- reigned approximately three centuries over an extensive area. Furthermore, the Saljuqs affected even the territories that they did not have any control over their history, such as al-Andalus, North Africa, and Egypt. This great influence of the Saljuqs' on the Islamic lands has taken as the main subject in various studies. Nevertheless, majority of these studies do not approach the Saljuqs from the theological angle; on the contrary, the literature mostly consists of studies evaluating the Saljuqs from other fields, such as political history, international relations, architecture, and handicrafts. Besides, in these limited studies, which were made with theological approach, tafsir (Qur'ānic exegesis) studies, took just a very insufficient place that it may be accepted as neglectable. In this thesis, we evaluate and examine the process of the tafsir studies on history and geography of Saljuqs. Initially, we determine boundaries of the concepts and environment. Latter, we shaped the paper with primary and secondary literature, such as tabaqats, history books, encyclopedias and other academic sources. At the end of this research, we detect that, the Saljuqs has a remarkable impact on the history of science, culture and civilization; as much as their great contributions on the development and circulation of the tafsir studies. Due to the madrasas they established, and the scholars and bureaucrats they educate, they interfere and influence the process of Islamic studies -and accordingly- tafsir studies. This period constitute the peak point of the theological studies for Saljuqs; however, the unproductive period that has start owing to the attacks of the Mongols and Crusaders', migrations, and the civil wars caused by dynastic fights for the throne, unfortunately continues until today.
The Commentators in Seljukids Period (XI-XIV age)
The Commentators in Seljukids Period (11-14 age)
Keywords: Tefsir; Selçuklular; Müfessirler; Kur’ân ilimleri; Tefsir ekolleri; Tafsir; The Saljuqs; Mufassirūn; Qur’ānic studies; Schools of tafsir